A Preliminary Study of 316L Stainless Steel Finishing Process by the Tumbling Method with Acrylic Abrasive Media - Finny Pratama Putera; S Suyitno (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
A certain level of roughness of the surface of a hip prosthesis is necessary to minimize wear on components. Smoothing of the surface roughness can be performed by the tumble finishing method. This research was aimed to figure out the effect of spindle rotary speed on the level of roughness of the test specimen surface. The test specimen was made of 316 stainless steel, which is one of the materials constituting the component of the femoral head in a hip prosthesis. The abrasive media used was acrylic type plastic with a 4-mm-diameter spherical profile. The results of this tumbling process experiment demonstrate that the effective speed at which the cover surface of the test specimen was smoothed was the spindle rotary speed of 125 rpm.